2011
DOI: 10.1007/s12562-011-0382-3
|View full text |Cite
|
Sign up to set email alerts
|

Otolith microstructure of brown sole Pseudopleuronectes herzensteini: validation of daily ring formation and the occurrence of microstructure denoting metamorphosis

Abstract: Brown sole Pseudopleuronectes herzensteini larvae and juveniles were reared to validate daily otolith ring formation. At 15°C, a check (a distinct ring) formed on the sagittae and lapilli at 6 days after hatching, and clear increments regularly formed outside the check. For both otoliths, the relationship between the number of days after hatching and number of increments was linear, and the slope of the line was approximately 1; therefore, daily formation was validated. At 12°C, the check formed on the lapillu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
14
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 33 publications
2
14
0
1
Order By: Relevance
“…It is suggested that when otolith microstructure is analysed in juvenile lapilli, blind‐side lapilli are suitable for this analysis because it is possible to measure the width of otolith rings along a single axis throughout the larval and juvenile stages, at least, for specimens <51·6 mm L S . A similar change in the shape of lapilli was reported for P. herzensteini , P. yokohamae and R. tapirina juveniles (Sogard, ; Joh et al , , ). Hence, bilateral asymmetry in juvenile lapilli is probably a common feature in flatfish species.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…It is suggested that when otolith microstructure is analysed in juvenile lapilli, blind‐side lapilli are suitable for this analysis because it is possible to measure the width of otolith rings along a single axis throughout the larval and juvenile stages, at least, for specimens <51·6 mm L S . A similar change in the shape of lapilli was reported for P. herzensteini , P. yokohamae and R. tapirina juveniles (Sogard, ; Joh et al , , ). Hence, bilateral asymmetry in juvenile lapilli is probably a common feature in flatfish species.…”
Section: Discussionsupporting
confidence: 81%
“…The AP were present on the outer edge of the sagittae of metamorphosing larvae and juveniles. The formation of AP has been reported in many flatfish species (Sogard, ; Mordin et al , ; Joh et al , , ) and the formation of AP in sagittae may be a common feature in flatfishes. Until the formation of AP, the rings form concentrically from the central core of the sagittae.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Such a change between life stages may cause short-term stagnation of length growth, because other adaptions to new lifestyle requirements (e.g., spindle shape, scales) were favoured over size increase. Beside clupeids, time-varying reduced growth during ontogeny can also be observed at the settlement of reef fishes (Wilson and McCormick 1997) and metamorphosis of flatfishes (e.g., Joh et al 2011). A reduction in length growth that is accompanied with a change in the relationship of fish and otolith length leads to complications in back-calculations of length like in Baltic sprat.…”
Section: Back-calculating Length Beyond Ontogenetic Transitionsmentioning
confidence: 99%
“…Therefore, larval growth increments could not be assigned to specific dates and instead, analyses were based on temperatures in fixed temporal windows across years. Some researchers (Sogard, 1991;May and Jenkins, 1992;Joh et al, 2011) have relied solely on flatfish lapilli due to the presence of clearer daily increments than observed in sagittae. In NRS, daily increments were consistently clearer in lapilli although there was no evidence of a metamorphosis check or zone, which was a primary focus of our study.…”
Section: Discussionmentioning
confidence: 99%